Nectar chemistry mediates the behavior of parasitized bees: consequences for plant fitness. Issue 2 (7th March 2016) - Richardson, Leif L.; Bowers, M. Deane; Irwin, Rebecca E.
Abstract: Plants produce an array of secondary metabolites that play important ecological roles as anti‐herbivore and anti‐pathogen defenses. Many herbivores experience physiological costs when they consume secondary metabolites, yet some also benefit, for example when these chemicals confer resistance to parasites and predators. Secondary metabolites are often present in nectar and pollen, which is paradoxical given that floral rewards are important in the attraction of mutualists rather than deterrence of antagonists. Motivated by studies of interactions among plants, herbivores, and parasites, as well as research showing that secondary metabolites can reduce bee disease, we characterized the occurrence of two iridoid glycosides, aucubin and catalpol, in floral rewards and other tissues of the bee pollinated plant, Chelone glabra . We then experimentally investigated effects of nectar iridoid glycoside concentrations on the foraging behavior of bumble bee pollinators naturally afflicted by a parasitoid fly and a protozoan intestinal parasite, and subsequent effects on an estimate of plant reproduction. We found that floral nectar had lower iridoid glycoside concentrations than leaves, pollen, and corollas, and that, compared to those plant parts, the relative ratio of the two primary iridoid glycosides, aucubin and catalpol, was reversed in nectar. Whether bees carried parasitoid fly larvae did not affect their response to nectar chemistry; however, there was a significant interaction between protozoan parasite infection and nectar treatment, with infected bees foraging longer at flowers with high compared to low nectar iridoid glycoside concentrations. Parasitized bees were also more likely to return to inflorescences with high iridoid glycoside nectar. Consequently, flowers in the high iridoid glycoside nectar treatment donated significantly more pollen to conspecific stigmas than did flowers in the low iridoid glycoside treatment, suggesting an increase in male plant fitness. Taken together, these results demonstrate that nectar secondary metabolites can mediate the behavior of pollinators with subsequent benefits for estimates of plant reproduction.